here it is...
2x + y = 6
x - y = -3
1) Solve one of the equations for one of the variables. Say, solve the first equation for y:
2) Substitute this expression for y into the other equation:
x - (6-2x) = -3
The equation becomes an equation in one variable only. Solve it for that vaiable:
x - 6 + 2x = -3
3x - 6 = -3
3x = -3+6
3x = 3
x = 1
3) Substitute the value that you found into ...
This posting offers help with using substitution or addition/elimination technique to solve a system of equations.